Vegan Triple-Ironman (Raw Vegetables/Fruits) - Roman Leischik; Norman Spelsberg (Case Reports in Cardiology)
Endurance sport requires a healthy and balanced diet. In this case report we present the findings of an ultra-triathlete (three times Ironman, means 11.4 km swim, 540 km bike, 125 km run in 41:18 h as a whole) living on a raw vegan diet and having finished the competitions under these nutritional conditions. To this end, the vegan ultra triathlete and a control group of 10 Ironman triathletes of similar age living on a mixed diet were investigated, using echocardiography and spiroergometry. In addition, blood samples were taken from the vegan athlete both in the sporting season and in the off-season. The vegan athlete showed no signs of dietary deficiencies or impaired health. In comparison with the control group, the vegan athlete showed a higher oxygen intake at the respiratory compensation point. This case demonstrates that even top-class sporting performance, like that of a three-time Ironman, is possible on a vegan diet. Whether a vegan diet offers advantages or disadvantages for the performance of endurance athletes remains an open question.